2011
DOI: 10.1111/j.1872-034x.2011.00847.x
|View full text |Cite
|
Sign up to set email alerts
|

Cancer preventive effect of pegylated interferon α‐2b plus ribavirin in a real‐life clinical setting in Japan: PERFECT interim analysis

Abstract: Several known risk factors for HCC contributed to HCC in patients who received PEG-IFN α-2b and RBV combination therapy, and ALT abnormality after the end of treatment contributes to the onset of HCC in both non-SVR and SVR patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…The association between response to PEG IFN/RBV and SNP associated with IL28B was concurrently reported by two other groups who also employed GWAS 8,9 . The IL28B polymorphism was highly predictive of the response to PEG IFN/RBV therapy in Japanese chronic hepatitis C (CHC) patients 10–12 . However, this was not always the case.…”
Section: Introductionmentioning
confidence: 84%
“…The association between response to PEG IFN/RBV and SNP associated with IL28B was concurrently reported by two other groups who also employed GWAS 8,9 . The IL28B polymorphism was highly predictive of the response to PEG IFN/RBV therapy in Japanese chronic hepatitis C (CHC) patients 10–12 . However, this was not always the case.…”
Section: Introductionmentioning
confidence: 84%
“…Many studies have reported that antiviral therapy is useful as a radical treatment for hepatitis C, and hepatocarcinogenesis can be inhibited by achieving SVR [6,22,23,24]. However, therapies involving IFN are sometimes challenging due to adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these results suggest that the carcinogenic process in patients with chronic HCV infection is enhanced by high levels and fluctuations of alanine aminotransferase, and indicate a close relationship between suppression of inflammatory necrosis of hepatocytes and a lower incidence of hepatocellular carcinoma in patients with HCV-associated chronic liver disease. Recent studies based on interferon plus ribavirin combination therapy also showed that the attainment of sustained virological response or lower levels of alanine aminotransferase after ribavirin combination therapy could reduce the rates of hepatocellular carcinoma [15,16], but the small numbers of patients with compensated cirrhosis (5% or less of all patients) were recruited. The present study 1 based on the patients with compensated cirrhosis showed that rates of sustained virological response and sustained biochemical response in HCV-2a/2b were high rates of 70 and 78%, and that rates of sustained biochemical response (57%) were significantly higher than those of sustained virological response (34%) in HCV-1b.…”
Section: Discussionmentioning
confidence: 99%